2020
DOI: 10.1039/c9ra10344a
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessing of soybeans (Glycine max L.) by solid-state fermentation with Eurotium cristatum YL-1 improves total phenolic content, isoflavone aglycones, and antioxidant activity

Abstract: Solid-state bioprocessing with Eurotium cristatum is an effective approach for the enhancement of total phenolic content, isoflavone aglycones, and antioxidant activity of soybeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 54 publications
6
54
0
Order By: Relevance
“…The increased flavonoid glucoside form and aglycon form increases antioxidant activities such as ABTS, DPPH, FRAP, and TFC, which may affect the antioxidant activity of RAC, as shown in the correlation network map (Figure 4). This phenomenon was also observed in a previous study that showed biotransformation of glucoside isoflavones to aglycones and increasing patterns in antioxidant activity according to fermentation time in soybean fermented with A. cristatus [31].…”
Section: Discussionsupporting
confidence: 85%
“…The increased flavonoid glucoside form and aglycon form increases antioxidant activities such as ABTS, DPPH, FRAP, and TFC, which may affect the antioxidant activity of RAC, as shown in the correlation network map (Figure 4). This phenomenon was also observed in a previous study that showed biotransformation of glucoside isoflavones to aglycones and increasing patterns in antioxidant activity according to fermentation time in soybean fermented with A. cristatus [31].…”
Section: Discussionsupporting
confidence: 85%
“…The Trolox equivalent values for yeast cell wall particles and native yeast were reported to be 0.20 and 7.48 μM, respectively ( 27 ). Chen et al ( 28 ) reported that Lactobacillus rhamnosus and Saccharomyces cerevisiae significantly improved FRAP in comparison to their non-fermented counterparts, and both activities were attributed to the released phenolics during the solid-state fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…The protease produced during the fermentation could effectively enhanced biological activity of the products ( 11 ). The formaldehyde method was used to determine the protease activity of P. yezoensis sauce ( 12 ).…”
Section: Methodsmentioning
confidence: 99%